σ-Bond electron delocalization of branched oligogermanes and germanium containing oligosilanes - Hlina, Johann (Inorganica Chim Acta, 2014)
In order to evaluate the influence of germanium atoms in oligo- and polysilanes, a number of oligosilane compounds were prepared where two or more silicon atoms were replaced by germanium. While it can be expected that the structural features of thus altered molecules do not change much, the more interesting question is, whether this modification would have a profound influence on the electronic structure, in particular on the property of σ-bond electron delocalization. The UV-spectroscopic comparison of the oligosilanes with germanium enriched oligosilanes and also with oligogermanes showed a remarkable uniform picture. The expected bathochromic shift for oligogermanes and Ge-enriched oligosilanes was observed but its extent was very small. For the low energy absorption band the bathochromic shift from a hexasilane chain (256 nm) to a hexagermane chain with identical substituent patterns (259 nm) amounts to a mere 3 nm.